Coaxial Fe3O4/CuO hybrid nanowires as ultra fast charge/discharge lithium-ion battery anodes - Saadat, Somaye (2013)
We report the facile, template free electrochemical fabrication of hierarchical Fe3O4/CuO hybrid wires, grown directly on a copper substrate. The electrodes are produced by the electrochemical deposition of Fe3O4 on CuO nanoneedle arrays, fabricated by anodization. The Fe3O4/CuO hybrid anodes displayed ultrafast charging/discharging properties and high rate capabilities, superior to those of their individual building blocks Fe3O4 and CuO. For example, at a current density of 820 mA g−1, the Fe3O4/CuO hybrid wires delivered high reversible specific capacity, good cycling stability (delivering 953 mA h g−1 discharge capacity with 98.7% Coulombic efficiency after 100 cycles) and excellent rate capability (319 mA h g−1 at 8200 mA g−1). The excellent performance of the Fe3O4/CuO hybrids comes from the intelligent integration of the two compatible components into unique hierarchical architectures with a high specific capacity, with one-dimensional CuO nanoneedle arrays electrochemically coated with mesoporous Fe3O4 nanocubes.